Estimation of Effective Wave Slope Coefficient of Ships with Large Breadth and Draught Ratio - Paroka, Daeng; Muhammad, Andi Haris; Rahman, Sabaruddin (Department of Naval Architecture - Diponegoro University, 2020)
One of parameters to estimate heel angle of a ship in beam seas is effective wave slope coefficient. In the weather criterion of IMO, the effective wave slope coefficient is determined as function of ratio between distance of center of gravity from the sea surface and the ship draught. The others methods could be used to estimate the effective wave slope coefficient are simplified strip theory and model experiment. A ship with shallow draught and large vertical center of gravity can have an effective wave slope coefficient larger than 1.0 if the coefficient is calculated by using the formulae of weather criterion. Therefore, an alternative method to estimate the coefficient is necessary when it is applied to ships with geometry characteristics different with those used to develop the formulae. This research conducts to estimate the effective wave slope coefficient using three different methods, namely the formulae of weather criterion, the simplified strip theory and model experiment. Results of the three methods may provide enough evidence about suitable method to estimate the effective wave slope coefficient of ships with breadth and draught ratio larger than 3.5 like the Indonesian ro-ro ferries. Results and discussion show that the effective wave slope coefficient obtained by using the formulae of weather criterion is larger compared to that obtained by using the simplified strip theory and the model experiment. Here, the result of simplified strip theory for wave frequency the same as the roll natural frequency of subject ship is similar with the result of model experiment. This results show that the simplified strip theory can be used as an alternative method to determine the effective wave slope of a ship with breadth and draught ratio larger than 3.5 if the result of model experiment does not available.